2016
DOI: 10.1038/srep25509
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule ameliorates ocular neovascularisation and synergises with anti-VEGF therapy

Abstract: Ocular neovascularisation underlies blinding eye diseases such as retinopathy of prematurity, proliferative diabetic retinopathy, and wet age-related macular degeneration. These diseases cause irreversible vision loss, and provide a significant health and economic burden. Biologics targeting vascular endothelial growth factor (VEGF) are the major approach for treatment. However, up to 30% of patients are non-responsive to these drugs and they are associated with ocular and systemic side effects. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 42 publications
2
73
0
Order By: Relevance
“…Many anti-angiogenic drugs have been suggested as potential therapeutic agents in ocular diseases, such as retinopathy of prematurity in children, proliferative diabetic retinopathy in adults, and age-related macular degeneration in the elderly [36,37]. Biologics targeting against HIF/VEGF pathway causing the overexpression of angiogenic genes are the major approach for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many anti-angiogenic drugs have been suggested as potential therapeutic agents in ocular diseases, such as retinopathy of prematurity in children, proliferative diabetic retinopathy in adults, and age-related macular degeneration in the elderly [36,37]. Biologics targeting against HIF/VEGF pathway causing the overexpression of angiogenic genes are the major approach for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interaction of Ang proteins and Tie-2 may be a potential target for therapies in retinal vascular complications [21]. Modulation of VEGF signaling and Ang-2 expression has been proposed as a tool to correct the cellular mechanisms involved in the pathophysiology of diabetic retinal and choroidal vascular diseases [36]. This study revealed that the up-regulation of both Ang-2 and Tie-2 was inhibited in high glucose-exposed endothelial cells treated with chrysin and retinas of diabetic mice orally administrated chrysin.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, eyes of anesthetised mice were dilated with 1% tropicamide solution (Alcon, Fort Worth, TX, USA) and lubricated with Gonak hypromellose ophthalmic solution (Akorn, Lake Forest, IL, USA). Horizontal and vertical OCT images were taken per lesion and L-CNV lesion volumes were obtained using the quantification method previously established [30,31]. To assess vascular leakage, fluorescein angiography was performed on day 14 post L-CNV by i.p.…”
Section: Laser-induced Choroidal Neovascularisationmentioning
confidence: 99%
“…Nevertheless, there have not been synthetic efforts towards such homoisoflavonoids since the synthesis of 4 and 9 was reported in 1971 [12]. A chemical synthesis of 5,6,7-trisubstituted homoisoflavonoids has the potential to provide a general and expedient entry into a plethora of analogues potentially with interesting biological activities [1315]. Herein we report the first synthesis of cremastranone's derivatives in three or four steps from the known 4-chromenone, involving a chemoselective 1,4-reduction and manipulation of protecting groups.…”
Section: Introductionmentioning
confidence: 99%